Hubungan Pengetahuan dan Tekanan Sosial dengan Perilaku Pencegahan Penularan HIV/AIDS pada Warga Binaan Pemasyarakatan Perempuan di Lapas Kelas IIB Padang Tahun 2022 - Hilda Hidayat; Sri Mindayani (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2022)
HIV/AIDS in Indonesia is concentrated in certain population groups who have a high risk of HIV transmission related to their behavior, one of which is Female Correctional Families (WBP). This study aims to determine the relationship between characteristics and social pressure with behavior to prevent HIV/AIDS transmission in prisoners in Lapas II B, Padang City. This type of research is analytic with cross sectional design. This research was conducted from September 2021 to February 2022 at Lapas II B, Padang City. The research population is 121 people and the sample is 70 people. Sampling was done by cluster sampling technique. Primary data collection was carried out by interview technique using a questionnaire. Data analysis includes univariate analysis and bivariate analysis. The results showed that there was no relationship between knowledge (P Value=0.256) and no relationship between social pressure (P Value=0.171). It is suggested to Correctional Institution Officers to collaborate with the Health Office, Puskesmas, Police, Ministry of Religion, community leaders and family members regarding efforts to prevent HIV/AIDS transmission behavior and motivate prisoners. It is hoped that the IIB prison leadership will make an empowerment program to improve skills and self-quality.